Contrasting Effects of Larval Escitalopram and Serotonin-Synthesis Inhibitor on Adult Phototaxis in Drosophila w1118 - Krams, Indrikis; Kolbjonoks, Vadims; Popovs, Sergejs; Munkevics, Māris; Krams, Ronalds; Trakimas, Giedrius; Rantala, Markus J.; Contreras-Garduño, Jorge; Jõers, Priit; Adams, Colton B.; Krama, Tatjana (MDPI, 2026)
Phototaxis, the movement toward or away from light, is a fundamental behavior with ecological and evolutionary relevance. In Drosophila melanogaster, phototactic choice shows individual variability and has been linked to serotonergic signaling. Using a high-throughput FlyVac assay to test single flies in parallel, we reared w1118 flies on (1) standard food (Control), (2) aMW (a serotonin-synthesis inhibitor), (3) 5-HTP (a serotonin precursor), or (4) escitalopram (a selective serotonin reuptake inhibitor, SSRI). Light-choice probability (LCP) did not differ between Control and aMW. LCP was lower in 5-HTP and escitalopram than in Control and aMW, and lower with escitalopram than with 5-HTP. Between-fly variability (MADn) differed across treatments: escitalopram exhibited higher dispersion than Control and aMW, whereas 5-HTP did not differ reliably from Control. These findings support the hypothesis that serotonin modulates behavioral predictability and mean choice bias; variability effects were compound-specific (escitalopram modestly increased MADn, whereas 5-HTP did not differ from Control). Given the rising costs and ethical constraints of vertebrate models, our results highlight Drosophila and FlyVac as a powerful, cost-effective system for investigating SSRI effects on decision phenotypes.